Aplasia of the vagina and uterus (Mayer-Rokitansky-Kustner-Hauser syndrome): etiology, pathogenetic aspects and theory of the formation of defect (literature review) - D A Kruglyak; N A Buralkina; M V Ipatova; Z K Batyrova; E V Uvarova (IP Berlin A.V., 2018)
The article provides data on the etiology and pathogenesis of genital malformation - vaginal and uterine aplasia (Mayer-Rokitansky-Kustner-Hauser syndrome) at the present stage.